Sex-specific strategy use and global-local processing: a perspective toward integrating sex differences in cognition - Pletzer, Belinda (Frontiers in Neuroscience, 2014)
This article reviews the literature on sex-specific strategy use in cognitive tasks with the aim to carve out a link between sex differences in different cognitive tasks. I conclude that male strategies are commonly holistic and oriented towards global stimulus aspects, while female strategies are commonly decomposed and oriented towards local stimulus aspects. Thus, the strategies observed in different tasks, may depend on sex differences in attentional focus and hence sex differences in global-local processing. I hypothesize that strategy use may be sex hormone dependent and hence subject to change over the menstrual cycle as evidenced by findings in global-local processing and emotional memory. Furthermore, I propose sex hormonal modulation of hemispheric asymmetries as one possible neural substrate for this theory, thereby building on older theories, emphasizing the importance of sex differences in brain lateralization. The ideas described in the current article represent a perspective towards a unifying approach to the study of sex differences in cognition and their neural correlates.